PERAN APARATUR SIPIL NEGARA SEBAGAI PELAYANAN PUBLIK GUNA MEWUJUDKAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK - Aisyah Dinda Karina; Muhammad Zainuddin; Muhammad Diego Armando (Smart Law Journal, 2024)
People are provided convenience in filling out administrative files to support their personal data in the current globalization period. Humans as a culture require these administrative files from the moment of their birth till their demise. Humans possess administrative tools, which are among the most significant items in the real world for carrying out daily tasks. Of course, in order for all societal levels to be able to gain these rights, the government as the holder of policies and regulations must play a part in completing these administrative files. In order to properly and accurately fulfill administrative files for all levels of society, the government, through the State Civil Apparatus (ASN), in this case Civil Servants (PNS) and Government Employees with Work Agreements (PPPK), must always collaborate. This study was conducted in order to gain a better knowledge of how the State Civil Apparatus functions as a government arm in carrying out the fundamental ideas of good governance. Researchers will employ a normative juridical approach, which entails doing research on the basis of legal sources and looking into relevant ideas, conceptions, and legal principles. Analytical descriptions will be used in this study to process research findings.